Avaliação do impacto das comorbidades na inflamação do Transtorno Bipolar - Juliana Lemos Rabelo (2024)
Introduction: Bipolar disorder (BD) is a chronic illness characterized by mood changes. Evidence suggests changes in pro-inflammatory cytokines in BD, especially during the manic and depression phases, with elevated levels of tumor necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL -6) and Interferon-gamma (IFN-γ). There appears to be a reduction in epidermal growth factor (EGF) levels in euthymic patients diagnosed with TB. Inflammation appears to mediate the relationship between the high prevalence of clinical comorbidities and TB, resulting in a higher frequency of disease episodes, greater severity of symptoms and a lower response to treatment. Patients diagnosed with TB have a higher prevalence of chronic comorbidities such as endocrine and metabolic cardiovascular diseases, associated with an increased risk of premature mortality in people diagnosed with TB. Objective: To evaluate the impact of clinical comorbidities on inflammation in euthymic patients diagnosed with TB. Method: This is an observational, exploratory, cross-sectional study, carried out with 47 patients diagnosed with TB and 28 individuals recruited from the community, matched by sex and age. The subjects underwent semi-standardized anamnesis, the Hamilton depression scale (HAM-D) and the Young mania scale (YOUNG). Vital data, blood pressure, abdominal circumference, hip circumference, weight, height and calculation of Body Mass Index (BMI) were measured. Cardiovascular Risk was used using the Framingham global risk score (ERG) and QRISK 3. The presence of MetS was determined based on the criteria of the National Cholesterol Education Program's Adult Treatment Panel III - modified NCEP ATP III and comorbidities using the Cumulative scale Illness Rating Scale (CIRS). Inflammatory markers (TNF-α, IL-1β, IL-6, IFN-γ, EGF and VEGF) were included in this analysis. Statistical analyzes were performed using SPSS version 25.0 software. Data normality was assessed using the Shapiro Wilk test. The Chi Square test was performed for comparisons of qualitative variables and the Mann Whitney test for quantitative variables. To evaluate the effect of the burden of comorbidities on inflammatory markers, analysis of covariance was performed. The significance level adopted for the analyzes was p < 0.05. Results: In the analysis of sociodemographic data, no differences were found between patients diagnosed with TB and controls in relation to sex and age. In the control group, 78.6% of individuals were female, with a median age of 42.5 years and a median of 15 years of education. The sample of patients diagnosed with TB was made up of 63.8% women with a median age of 52 years and an average of 19 years of education. Patients diagnosed with TB had a median diagnosis of 19 years. No difference was observed when diagnosed with hypertension, diabetes, or obesity. Patients with TB had a higher prevalence of MetS diagnosis (44.7%) compared to the control group (7.1%) (p = 0.001) and did not differ in relation to the Framingham ERG (p = 0.73) and QRISK-3 (83%) (p= 0.14). 87.2% of patients diagnosed with TB and 82.1% of controls were classified as low risk by the ERG score. Patients diagnosed with TB had a greater burden of comorbidities related to diseases quantified by the CIRS scale (p < 0.0001). Patients diagnosed with TB did not differ from controls in relation to TNF-α (p = 0.08), IL-6 (p = 0.80), IL-1β (p = 0.71), IFN-γ (p = 0.76), (EGF) (p = 0.93), (VEGF) (p = 0.37). Individuals with moderate comorbidities, according to the CIRS scale, had higher levels of IFN-γ when compared to individuals without comorbidities (p = 0.040). Conclusion: The results suggest that IFN-γ may be involved in comorbidities in patients diagnosed with TB.